Comparative Test on the Bond Damage of Steel and GFRP Bars Reinforcing Soft Rock Slopes - Xinrong He; Guowei Li; Sidi Kabba Bakarr; Jiantao Wu; Wei Yu (Applied Sciences, 2021)
Soft rock slopes were anchored with traditional steel bars and new Glass Fibre Reinforced Polymer (GFRP) bars. The difference in the anchorage performance of the two kinds of anchorage elements in soft rock and expansive soil was studied by an in-situ test. The results show that cyclic load can aggravate the bond damage of the interface between grouting body and both kinds of bars used in soft rock. Compared with the number of cyclic loads applied, the previous maximum load is the main factor that influences the bond damage of the anchorage bar. Under constant loading, the interface bond behaviour of GFRP bar is better than the steel bar. Because of the small difference in elastic modulus between the GFRP bar and the grouting body, the interface bond around the GFRP bar can invoke more resistance of the grouting body efficiently which demonstrates its more effective anchorage performance than the steel bar under the same conditions. The anchorage structure of steel bar in soft rock can generate larger interfacial relative displacement with increasing load than the GFRP bar in the anchorage section, even though the elastic modulus of steel is much larger than GFRP. In the expansive soil, the anchorage structure deformations of steel and GFRP bars are almost the same because of the weaker bond at the interface of the grouting body and the surrounding soil than that of the bar interface. Under the ultimate loading of the anchorage structure in soft rock, the steel bar with 450 MPa which is less than its ultimate strength shows the failure of the bar body pulling-out, and the GFRP bar with 508 MPa which is larger than its ultimate strength shows the failure of the bar body by fracture. The steel bar anchorage structure in soft rock is destroyed at the interface around the grouting body. The results show that the GFRP bar performs more efficiently than the steel bar.